Survival Analysis on Breast Cancer Incidences in Ikeja, Lagos Nigeria Using Kaplan Meier and Cox Proportional Hazard Techniques - M., Ajao Olutunde; A., Afariogun David; O., Ayeni Elizabeth; O., Egbe Kehinde (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study investigates breast cancer survival outcomes in relation to treatment types, using retrospective data sourced from the Oncology Department at Lagos State University Teaching Hospital (LASUTH). Employing survival analysis techniques—specifically the Kaplan-Meier method for estimating survival probabilities and the Cox Proportional Hazards model to examine the influence of demographic factors—the study measured survival time from diagnosis to either death or the last known follow-up. The event of interest was the patient’s vital status. Results indicated that while breast cancer affects all genders, females are nearly twice as likely to be diagnosed as males. Age was also a significant determinant of survival, with older patients exhibiting a higher risk of mortality, as shown by increasing hazard ratios. These findings highlight the importance of early detection, particularly in younger individuals, as a critical strategy to enhance survival prospects.